A psychosomatic approach to the diagnosis and treatment of anxiety in patients with chronic noncommunicable diseases - Chaban, Олег; Khaustova, Олена; Sak, Леся (Psychosomatic Medicine and General Practice, 2020)
Background. Anxiety is a normal protective mechanism that a person acquired during evolution and is the very first mental reaction that occurs in response to a disease or precedes it. When anxiety becomes long-term and pronounced, it is anxiety as a disorder that negatively affects a person’s quality of life, disrupting his physical, mental and social functioning. The early diagnosis and treatment of anxiety in patients with chronic noncommunicable diseases (NCD) is important for preventing chronic and somatization of mental disorders, reducing and preventing complications of NCD. At the primary care level, naturopathic drugs occupy an important place in the treatment of subclinical anxiety disorders or somatized anxiety disorders. A number of clinical studies prove the anxiolytic and anti-stress effect of ashwagandha extract L-thianine and passiflora extract (Passiflora incarnata), which were combined in the phytotherapy complex Anxiomedin®. Methods and materials. An 4-week study tested the efficacy and safety of Anxiomedin in the treatment of psychosomatic manifestations of anxiety in 75 adult ambulatory patients with NCD. Patients were examined according to the HADS Hospital Anxiety and Depression Scale, a four-dimensional questionnaire for assessing distress, depression, anxiety and somatization 4DSQ, the Sax-Sydney SSCT method of incomplete sentences; blood pressure (BP) and pulse were also monitored. Results. At 4 weeks of therapy, patients with NCD and subclinical anxiety had a reduction: somatization on the 4DSQ scale (-57.7%), anxiety on the HADS scale (-58.6%), conflict index according to the SSCT method (-42.3%) , sympathicotonia (decrease in heart rate by 24.4%). Also according to the SSCT method, significant conflict zones that have undergone a significant reduction in the course of therapy were: attitude to the future (p <0.01); fears and anxieties (p <0.01); attitude to the disease (p <0,01); attitude to himself (p <0,05). No significant side effects were detected during the study. Conclusion. There is a two-way link between anxiety and NCD regarding the onset and development of mental and physical disorders. In the treatment of subclinical and somatized anxiety, especially in primary care, naturopathic drugs, such as Anxiomedin, have proven to be effective and safe.